(untitled) (TAMADDUN NURI JURNALI, 2024)
The article discusses the contributions of Doctor of Philology Kalli Ayimbetov, one of the scholars who laid the foundation for the study of Karakalpak literature and literary language, as well as his research on the contributions of national intellectuals.